Sour grapes - Lennard, Laurie 1958-; David, Larry 1947-; David, Larry 1947-; Weber, Steven 1961-; Bierko, Craig 1964-; Keeslar, Matt 1972- (Warner Home Video, 1997)
They're cousins and best pals...till debt do them part! Richie figures he owes cousin Evan 50 cents. Evan figures it's more like, oh, a little over (Dollar sign)218,000.A (Dollar sign)436,000 slots jackpot-and the two quarters Richie bummed from Evan to win it.